Modelling factors connected with the effect of international migration for security and economy - Berezka, Kateryna; Kovalchuk, Olha (Modelowanie czynników związanych ze skutkami międzynarodowej migracji dla bezpieczeństwa i gospodarki, 2019)
This article concerns research conducted on the casual connections between modern global migratory processes and basic socio-economic and safety indexes for countries around the world countries. On the basis of new official dataset there was developed a cluster model of countries distributed according to the basic indicators which characterize migratory streams (emigration/immigration), safety and macroeconomic indexes, related to the international migration. It is established that, in general, people are moving to safer countries that can provide them with better opportunities and social guarantees. The factor models for emigration and immigration processes, and international migration in general have been constructed. The main factors that prompt people to change their place of residence and the economic and safe effects of unprecedented levels of international migration are revealed. The empirical research examined in this paper confirmed the causal link between the volumes of international migration flows and the growth of Foreign Direct Investment in home countries and the reduction of security in host countries. The lack of statistical connection between immigration and emigration flows has been established
Econometrics = Ekonometria, 2019, Vol. 23, No. 4, s. 30-42
Keywords: international migrations; economic growth; safety; climate change; modeling; migracja międzynarodowa; wzrost gospodarczy; bezpieczeństwo; zmiana klimatu; modelowanie